Image-guidance and computational modeling to develop and characterize microwave thermal therapy platforms - Faridi, Pegah (Kansas State University, 2020)
This dissertation focuses on the development of magnetic resonance imaging (MRI)-guided microwave thermal therapy systems for driving experimental studies in small animals, and to experimentally validate computational models of microwave ablation, which are widely employed for device design and characterization. MRI affords noninvasive monitoring of spatial temperature profiles, thereby providing a means to to quantitatively monitor and verify delivery of prescribed thermal doses in experimental studies and clinical use, as well as a means to validate thermal profiles predicted by computational models of thermal therapy. A contribution of this dissertation is the development and demonstration of a system for delivering mild hyperthermia to small animal targets, thereby providing a platform for driving basic research studies investigating the use of heating as part of cancer treatment strategies. An experimentally validated 3D computational model was employed to design and characterize a non-invasive directional water-cooled microwave hyperthermia applicator for MRI guided delivery of hypethermia in small animals. Following a parametric model-based design approach, a reflector aperture angle of 120°, S-shaped monopole antenna with 0.6 mm displacement, and a coolant flow rate of 150 ml/min were selected as applicator parameters that enable conformal delivery of mild hyperthermia to tumors in experimental animals. The system was integrated with real-time high-field 14.1 T MRI thermometry and feedback control to monitor and maintain target temperature elevations in the range of 4 – 5 °C (hypethermic range). 2 - 4 mm diameter targets positioned 1 – 3 mm from the applicator surface were heated to hyperthermic temperatures, with target coverage ratio ranging between 76 - 93 % and 11 – 26 % of non-targeted tissue heated. Another contribution of this dissertation is using computational models to determine how the fibroids altered ablation profile of a microwave applicator for global endometrial ablation. Uterine fibroids are benign pelvic tumors located within the myometrium or endometrium,and may alter the profile of microwave ablation applicators deployed within the uterus for delivering endometrial ablation. A 3D computational model was employed to investigate the effect of 1 – 3 cm diameter uterine fibroids in different locations around the uterine cavity on endometrial ablation profiles of microwave exposure with a 915 MHz microwave triangular loop antenna. The maximum change in simulated ablation depths due to the presence of fibroids was 1.1 mm. In summary, this simulation study suggests that 1 – 3 cm diameter uterine fibroids can be expected to have minimal impact on the extent of microwave endometrial ablation patterns achieved with the applicator studied in this dissertation. Another contribution of this dissertation is the development of a method for experimental validation of 3D transient temperature profiles predicted by computational models of MWA. An experimental platform was developed integrating custom designed MR-conditional MWA applicators for use within the MR environment. This developed platform was employed to conduct 30 - 50 W, 5 - 10 min MWA experiments in ex vivo tissue. Microwave ablation computational models, mimicking the experimental setting in MRI, were implemented using the finite element method, and incorporated temperature-dependent changes in tissue physical properties. MRI-derived Arrhenius thermal damage maps were compared to Model-predicted ablation zone extents using the Dice similarity coefficient (DSC). Mean absolute error between MR temperature measurements and fiber-optic temperature probes, used to validate the accuracy of MR temperature measurements, during heating was in the range of 0.5 – 2.8 °C. The mean DSC between model-predicted ablation zones and MRI-derived Arrhenius thermal damage maps for 13 experimental set-ups was 0.95. When comparing simulated and experimentally (i.e. using MRI) measured temperatures, the mean absolute error (MAE %) relative to maximum temperature change was in the range 5 % - 8.5 %.
Keywords: Computational modeling; Microwave; Thermal therapy; Image-guidance; Ablation